1999
DOI: 10.1002/(sici)1099-081x(199903)20:2<69::aid-bdd153>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and disposition of a tripeptoid and a tetrapeptide in the rat

Abstract: ABSTRACT:The present study is concerned with the absorption and disposition of a tripeptoid (N-substituted glycine derivative) and a tetrapeptide in the rat. The two compounds have similar backbone structures but differ with respect to the presence or absence of peptide bond. ) and intravenously (i.v.) (30 or 3 mg kg − 1 ) to Sprague Dawley rats. Blood, urine and feces were collected at designated times for radioactivity and parent drug analysis. The intestinal absorptive clearances of the tripeptoid and tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Antifungal peptides also generally act through membrane disruption, but may also cause fungal cell death through cell wall disruption or through intracellular (IC) targets that result in ROS generation or programmed cell death . Reports of peptoids in vivo indicate that they have poor oral bioavailability, excellent tissue absorption, slow elimination through the feces, long half‐lives, and limited toxicity, at least when tested acutely . One of these studies demonstrates the in vivo antibacterial efficacy of a peptoid, with an average two log order reduction in bacterial counts in mice compared to saline controls .…”
Section: Introductionmentioning
confidence: 72%
“…Antifungal peptides also generally act through membrane disruption, but may also cause fungal cell death through cell wall disruption or through intracellular (IC) targets that result in ROS generation or programmed cell death . Reports of peptoids in vivo indicate that they have poor oral bioavailability, excellent tissue absorption, slow elimination through the feces, long half‐lives, and limited toxicity, at least when tested acutely . One of these studies demonstrates the in vivo antibacterial efficacy of a peptoid, with an average two log order reduction in bacterial counts in mice compared to saline controls .…”
Section: Introductionmentioning
confidence: 72%
“…Peptoid analogs have shown higher selectivity, 15 improved potency 15 and superior pharmacological properties. 16,17 N a -Methylation (Fig. 1) is a powerful tool for structure-activity relationship studies and is often used to examine the effects of local backbone modifications on the potency of a known peptide sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from toxicity, the metabolic fate of peptoids needs to be determined through biodistribution studies. Tse and co-workers in 1999 showed that a trimer peptoid had low oral absorption and was excreted intact into the feces in 2 h [157]. To understand the fate of the peptoids in vivo, similar detailed studies need to be conducted using structurally and sequentially different, and active and inactive peptoids.…”
Section: Discussionmentioning
confidence: 99%